Characteristics of strike-slip fault-related reservoirs and the significance for hydrocarbon accumulation in the central Tarim Basin: Insights from the modern karst model - Ning, Fei; Lin, Huixi; Zhou, Cunjian; Yun, Jinbiao; Li, Peng; Song, Haiming (Frontiers in Earth Science, 2022)
Proven to be closely linked to hydrocarbon accumulation, the strike-slip faults are important hydrocarbon accumulation zones. In order to clarify the controlling effects of strike-slip faults on reservoirs, characteristics of two types of reservoirs, including strike-slip fault-controlled fracture-caverns and strike-slip fault-dissolved fracture-caverns in the central Tarim Basin, are delineated through detailed analyses of seismic data, tectonic evolution, and observations of core and thin section. High-density electrical logging was utilized for the modern karst area of South China to identify the development characteristics of the fractured-cavernous carbonate reservoirs. The development model of modern karst reservoirs was applied in the study of the Ordovician carbonate paleokarst in Tarim Basin to build the karst reservoir development model related to strike-slip faults. Modern karst investigation confirmed that the network of fracture systems formed by strike-slip faults was conducive to developing karst pores, while the tectonic slope provided hydrodynamic conditions for karstification. The karst fracture formed along the dissolved fractures at the top of the cave is not easily filled with debris, making it an important reservoir space outside the large karst caves. The Ordovician epikarst fracture-cavernous system is an important reservoir in the area from Shuntuoguole slope in the north of Tazhong uplift to the Tabei Uplift of the Tarim Basin. The reservoir, strike-slip faults and unconformities together constitute a three-dimensional hydrocarbon accumulation system, which facilitates the migration and accumulation of oil and gas from deep source rock to Ordovician karst fracture-caverns and plays a significant role in hydrocarbon migration and accumulation.